2020
DOI: 10.3389/fimmu.2020.02152
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Trimeric CO-26K-Equivalent Epitope Induced Neutralizing Antibodies Against Porcine Epidemic Diarrhea Virus

Abstract: Porcine epidemic diarrhea virus (PEDV) is a causative agent of a highly infectious disease with a high mortality rate, especially in newborn piglets in Asian countries resulting in serious economic loss. The development of a rapid, safe, effective and cost-efficient vaccine is crucial to protect pigs against PEDV infection. The COE antigen is regarded to be a major target for subunit vaccine development against PEDV infection. The naturally assembled COE protein forms a homotrimeric structure. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
0
18
1
Order By: Relevance
“…The neutralizing epitope derived from CV777 strain, COE, was fused to the polymeric Fc scaffold of IgG, as a new and promising vaccine platform for induction of both systemic and mucosal immune responses via the oral route. Our choice of antigen was the COE epitope containing sequence, which was demonstrated recently to induce PEDV neutralizing antibodies in mice when expressed in plants in native trimeric form (Ho et al, 2020). However, we emphasize that our primary aim was to develop a suitable vaccine platform against this and similar veterinary pathogens, rather than a ready-made vaccine, as that would require further modifications, including inclusion of other portions of the S protein as well as different variants of the virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutralizing epitope derived from CV777 strain, COE, was fused to the polymeric Fc scaffold of IgG, as a new and promising vaccine platform for induction of both systemic and mucosal immune responses via the oral route. Our choice of antigen was the COE epitope containing sequence, which was demonstrated recently to induce PEDV neutralizing antibodies in mice when expressed in plants in native trimeric form (Ho et al, 2020). However, we emphasize that our primary aim was to develop a suitable vaccine platform against this and similar veterinary pathogens, rather than a ready-made vaccine, as that would require further modifications, including inclusion of other portions of the S protein as well as different variants of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, COE epitope antigen of the S1 protein of PEDV, which is responsible for inducing neutralizing antibodies (Chang et al, 2002;Chang et al, 2019;Ho et al, 2020;Sun et al, 2008), was used to test the poly-Fc based vaccine against swine infection. The COE and PIGS fusion protein were transiently expressed in Nicotiana benthamiana plants and both systemic and oral immunogenicity were analyzed in the mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the immunogenic analysis of the trimerized S protein showed that the protein elicited high levels of the S protein-specific IgG and the neutralizing antibodies against PEDV infection. In a previous study, three doses of a crude plant extract containing 18.76 μg of trimerized CO-26K equivalent epitopes induced a geometric mean neutralizing antibody titer of 57.6 in mouse serum, which was comparable to that of a commercial vaccine [ 14 ]. In addition, administration of the B-cell epitope of PEDV presented on hepatitis B virus-like particles at 20 μg dosage resulted in average neutralizing antibody titers between 20 and 30 [ 46 ].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, there are many reports that the neutralizing epitopes are in the S protein [ 10 – 13 ]. Notably, it has been reported that several neutralizing epitopes are concentrated in a region called the CO-26 K equivalent epitope (COE), which contains amino acid residues 499–638 [ 10 , 14 ] as a priority candidate region. In addition, the N-terminal domain of the S protein, which is unique to the genus Alphacoronavirus, has been reported to play an important role in PEDV infection in the intestine, and this second candidate region is thought to have the ability to bind to a type of sialic acids unique to the intestine [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Later work involved the expression of an S protein epitope fused to CTB either transiently in N. benthamiana [ 79 ] or transplastomically in Nicotiana tabacum [ 80 ]. More recently, the expression of the COE synthetic epitope fused to a trimerization motif (C-terminal isoleucine zipper trimerization motif GCN4pII) has been expressed transiently in N. benthamiana and was shown to stimulate neutralising antibody production in mice [ 81 ]. Moreover, the much larger S1 coding region was expressed in transgenic maize and was shown to elicit a neutralising antibody response in pigs after oral administration [ 82 ].…”
Section: Coronavirusesmentioning
confidence: 99%